2006
DOI: 10.1128/jvi.02601-05
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus Outer Capsid Protein μ1 Induces Apoptosis and Associates with Lipid Droplets, Endoplasmic Reticulum, and Mitochondria

Abstract: The mechanisms by which reoviruses induce apoptosis have not been fully elucidated. Earlier studies identified the mammalian reovirus S1 and M2 genes as determinants of apoptosis induction. However, no published results have demonstrated the capacities of the proteins encoded by these genes to induce apoptosis, either independently or in combination, in the absence of reovirus infection. Here we report that the mammalian reovirus 1 protein, encoded by the M2 gene, was sufficient to induce apoptosis in transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 71 publications
4
105
0
Order By: Relevance
“…8B], which sedimented through the gradient to the bottom fractions without interaction with low-density fractions.) Intimate involvement of LD components with viral replication has previously been demonstrated for hepatitis C virus (HCV) (8,29,38,48), for the related GB virus B (29), for dengue virus (50), and to some extent for orthoreovirus (12). Interaction of the 2C protein of human parechovirus 1 with LDs has been observed (31); however, the significance of this interaction for viral replication is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…8B], which sedimented through the gradient to the bottom fractions without interaction with low-density fractions.) Intimate involvement of LD components with viral replication has previously been demonstrated for hepatitis C virus (HCV) (8,29,38,48), for the related GB virus B (29), for dengue virus (50), and to some extent for orthoreovirus (12). Interaction of the 2C protein of human parechovirus 1 with LDs has been observed (31); however, the significance of this interaction for viral replication is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Although engagement of RIG-I and IPS-1 activates NF-B by some agonists (3, 7), we found that reovirus activates NF-B independently of RIG-I and IPS-1. The reovirus 1 protein is sufficient to induce apoptosis when expressed ectopically in cell culture (61), implicating 1 in reovirus-induced NF-B activation. We hypothesize that 1 engages a cellular kinase that activates IKK␣/IKK␥ complexes or engages the IKKs directly to mediate NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether T1 and T3 reovirus strains differ in the capacity to replicate in the murine respiratory tract, we inoculated CBA/J mice intranasally with 10 7 PFU of T1L, T3D C , or T3D F and quantified viral titers in the lungs at days 1, 3, and 5 postinoculation. Since the T3D C and T3D F isolates of prototype reovirus strain T3D display a variety of distinct in vitro phenotypes (41)(42)(43), both isolates were used in our study. We found that inoculation with T1L produced significantly higher titers in the lungs than did T3D F (Fig.…”
Section: Resultsmentioning
confidence: 99%